2011
DOI: 10.2172/1062522
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Uranium Polymorphs

Abstract: Executive SummaryThe UO 3 -water system is complex and has not been fully characterized, even though these species are common throughout the nuclear fuel cycle. As an example, most production processes for UO 3 result in a mixture of up to six or more different polymorphic phases, and small differences in these conditions will affect phase genesis that ultimately result in measureable changes to the end product. As a result, this polymorphic feature of the UO 3 -water system may be useful as a means for determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 3 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…The Raman spectrum of γ-UO3 was observed by Armstrong et al 51 and Sweet et al [1][2] . A strong band was observed at 766 cm -1 , a medium strength band at 335 cm -1 , and weaker bands appear at 690, 483, 235, 103 and 51 cm -1 .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The Raman spectrum of γ-UO3 was observed by Armstrong et al 51 and Sweet et al [1][2] . A strong band was observed at 766 cm -1 , a medium strength band at 335 cm -1 , and weaker bands appear at 690, 483, 235, 103 and 51 cm -1 .…”
Section: Introductionmentioning
confidence: 84%
“…Fig. 6 shows the experimental Raman spectrum of γ-UO3 obtained by Sweet et al, [1][2] together with the calculated one. A summary of the experimental and calculated spectra is shown in Table 6, as well as the assignments of the vibrational modes derived from the calculations.…”
Section: Iii1 Structurementioning
confidence: 93%
See 1 more Smart Citation
“…This procedure returned a density closer to experimental observation, 7.40 gcm -3 , and a greater number of uranyl bonds in the final relaxed structure (Figure 2b). 10 There appeared to be, therefore, a negative correlation between the fully relaxed supercell density and propensity for uranyl bonding in this simulation study. This can be explained by the nature of the uranyl bonds observed in the simulated structures: the structure can be described as uranyl units with a variable degree of interconnection through shared equatorial oxygens, similar to the description of U2O7 by Odoh et al The uranyl bonds are observed where the oxygen is non-bridging to another monomer unit -a more prevalent observation in the lower density, lower network connectivity structure.…”
Section: Main Bodymentioning
confidence: 59%
“…Initial densities of 6.80 g/cm 3 and 1.60 g/cm 3 were trialled; while the former is the experimental density for this compound, it has previously been reported that lower densities, such as the latter, are required when modelling amorphous structures. [10][11][12] 20 different randomised structures were produced to ensure that the amorphous nature of the system is adequately captured. 12,13 Trials with 72-atom supercells were also carried out to understand the impact of system size on the final relaxed structure of the compound.…”
Section: Main Bodymentioning
confidence: 99%